(untitled) (Third Sector Social Economic Review, 2025)
The branding process of banks is directly linked not only to creating a visual identity but also to customer loyalty, trust, and financial stability. Today, banks maintain their traditional brand identities by emphasizing their corporate structures and deep-rooted histories, while also embracing modern banking by adapting to digitization processes. This study focuses on the branding process of Ziraat Bankası, which was named Türkiye’s most beloved bank in the “Bank” category of Türkiye’s Lovemarks for the ninth consecutive year as of 2024. The process is analyzed from the perspectives of corporate communication, customer loyalty, and digital transformation. In the research, an in-depth interview technique, a qualitative data collection method, was utilized. Within this scope, communication was established with managers actively involved in the corporate identity and branding process of the bank. The interview questions were prepared in a semi-structured format, capable of highlighting rich narratives, personal insights, and contextual details. The questions were framed around themes such as corporate communication management, the branding process (brand value creation, sustainable brand loyalty), and social media strategies. The recorded responses were transcribed and used in the study. In this context, the data were summarized and interpreted according to the themes determined by the descriptive analysis technique. The research identified Ziraat Bankası’s extensive service network across the country and its status as a public bank as factors that enhance customer trust and loyalty. Additionally, the effective use of social media strategies enables the bank to evaluate customer feedback easily, improve service processes, and manage crises more swiftly. The branding of banks not only strengthens customer relationships but also contributes to gaining a competitive advantage and ensuring financial stability. The example of Ziraat Bankası highlights the importance of strategies that strengthen brand value by harmonizing traditional and modern banking approaches. The study reveals that to create a sustainable brand value, banks must manage corporate communication, customer satisfaction, and digital transformation processes with an integrated understanding.